Amphiphilic polyesters bearing pendant sugar moieties: Synthesis, characterization, and cellular uptake - Peng, Kang-Yu; Hua, Mu-Yi; Lee, Ren-Shen (Carbohydrate Polymers, 2014)
•Amphiphilic block-graft (PαN3CL-g-Sugar)-b-PCL polymers were synthesized.•Glycosylated polymers can be used in biorecognition applications, and has low cytotoxicity.•Micelles facilitated an improved uptake of DOX and entreated the nuclei by endocytosis. Ring-opening polymerization (ROP) and “click” reactions were used to prepare a series of amphiphilic block-graft (PαN3CL-g-Sugar)-b-PCL polymers. The glycosylated RO-(PαN3CL-g-Sugar)-b-PCL polymers formed micelles with critical micelle concentrations (CMCs) in the range of 4.9–23.2mgL−1 in the aqueous phase. The mean diameters of the micelles were between 21nm and 125nm, considerably lower than the 200nm diameter at which the uptake of micelles by the reticuloendothelial cells becomes compromised. Selective lectin-binding experiments confirmed that glycosylated RO-(PαN3CL-g-Sugar)-b-PCL can be used in biorecognition applications, and in vitro cell-viability assay showed that RO-(PαN3CL-g-Sugar)-b-PCL has low cytotoxicity. Micelles loaded with doxorubicin (DOX) facilitated an improved uptake of DOX by HeLa cells that was completed within 1h, and the endocytosed-DOX successfully reached intracellular compartments and entered nuclei.